Studies on the Vegetation of Salem District - Shankarnarayan, K. A.; Dabholkar, M. V. (Indian Forester, 1959)
The situation, topography geology arid climate of Salem district are presented. Based on Champion’s classification the following types are met with, viz. (1) Southern thorn Forest, (2) Southern Dry Deciduous, (3) Southern Dry Evergreen, and (4) Southern Evergreen. The Southern thorn Forest comprises two sub-types namely: (a) Acacia-Pterolouium type and (b) Albi ia-Chloroxylon type. In the Dry Deciduous forests we encounter sub-types of Anogeissus and Shorea talura. The Dry Evergreen mainly consists of Hardwickia binata. The Southern Evergreen has predominantly Syzygium-Wendlandia type. The floristic composition of each type and sub-type is presented in detail.